Inverse analyses of disk infiltrometer tests - Leong, Eng Choon (2013)
The disk infiltrometer is a simple device used to measure hydraulic properties of unsaturated soils at low suctions. Saturated coefficient of permeability can be estimated from the coefficients of permeability measured at low suctions. However, there are several methods to calculate the hydraulic properties from disk infiltrometer tests. In this paper, inverse analyses of disk infiltrometer tests on compacted residual soil samples were performed. The estimated unsaturated hydraulic parameters were compared with those obtained experimentally. The results show that it is possible to obtain the soil-water characteristic curve accurately from the inverse analyses of disk infiltrometer tests.